A combined perception and needs assessment study of home based palliative care among patients with life-threatening diseases attending the Federal Medical Centre Abeokuta, Nigeria - Oyebola, Folaju Olusegun (Department of Public Health and Family Medicine, 2015)
Includes abstract.